EFFECT OF GLOMUS MOSSEAE, AZOTOBACTER CHROOCOCCUM AND VERMICOMPOST TEA ON SOME RHIZOSPHERE CHARACTERS AND MYCORRHIZAL DEPENDENCY OF CUCUMBER PLANTS - Z. H. Al-Rawi; J. S. Alkobaisy (مجلة الأنبار للعلوم الزراعية)
An experiment was carried out in a greenhouse (sandy loam soil) at the College of Agriculture, University of Anbar, to test the effect of the fungi Mycorrhiza type Glomus mosseae, Azotobacter bacteria type Azotobacter chroococcum and Vermicompost tea in the properties of the rhizosphere, namely the length and weight of the root system, the number of bacteria, the percentage of root infection with Mycorrhiza fungus, and the mycorrhiza dependence of the root and vegetative system and the yield of the cucumber plant Cucumis sativus L. A factorial experiment of two factors was designed. The first factor is a combination of mycorrhiza (M) of 35 g plant-1, azotopacter (A) 15 ml plant-1 with a microbial density of 2.2×109 cfu ml-1, and phosphate rock (R) of 40 g plant-1 added with half of the mineral recommendation individually with their interactions. The second factor is three concentrations: 0, 5, and 10% of vermicompost tea sprayed on the plant. The experiment was designed with a randomized, completely-blocked design (RCBD) with three replications. The seeds of the cucumber plant were planted on September 15th, 2022, and the service operations were conducted for the crop and continued until December 15th, 2022. The length and weight of the root system, the number of bacteria, the percentage of root infection with Mycorrhiza fungus, and the mycorrhizal dependency of the root system, vegetative and yield were measured. The results proved that the use of mycorrhiza, acetobacter bacteria, and phosphate rock with half mineral recommendation (MAR) and spraying of vermicompost tea at a concentration of 10% are the best significantly in increasing dry weight and height of the root system and in increasing the number of total bacteria. It showed significant differences between mycorrhiza, acetobacter, and vermicompost tea. The treatment resulted in the highest dry weight of the total root, 84.53 g, and the longest root length recorded was 71.73 cm. The highest total bacterial count was 8.74 log CFU g-1 soil. This was followed by adding Microrizae with phosphate rock and half the recommended mineral application (MR) with 10% vermicompost tea. Microrizae were added with Azotobacter bacteria and half the recommended mineral application (AR) with 10% vermicompost tea. Microrizae was treated with phosphate rock supplemented with half the recommended fertilizer application (MR) with 10% vermicompost tea. Then, the treatment of Microrizae with Azotobacter was supplemented with half the recommended fertilizer application (MA) with 10% vermicompost tea. Next, the Microrizae (M) and Azotobacter (A) treatments were applied individually. Finally, the chemical fertilizer treatment (S) yielded the lowest values for the mentioned soil and plant properties. A significant effect was observed in the percentage of achieved infection rate when using the root fungal inoculums, which reached 80.16% compared to only 5.50% without adding the root fungal inoculums. Based on the dry weight of the plastic greenhouse's total root, shoot, and yield, the mycorrhizal dependency percentage for cucumber plants was 52.3%, 57.8%, and 45.3%, respectively